A new record of fossil wood of Vochysiaceae from the Upper Pleistocene (Arroyo Feliciano Formation), Argentina, South America - Moya, Eliana Vanesa (2015)
A new species of Qualeoxylon Suguio & Mussa is described from the Late Pleistocene Arroyo Feliciano Formation of the Gualeguay Basin on eastern Argentina. It is the second record of this genus in South America and was previously only known from Late Eocene to Early Miocene (late Pleistocene for some authors) on the Itaquaquecetuba Formation, São Paulo, Brazil. This new fossil species was recovered in the Consorcio Paso Sociedad fossil locality (Federal, Entre Ríos, Argentina). Wood anatomical features suggest a close relationship with Vochysiaceae and is an affi nity with the extant genus Qualea. This fossil wood is consistent with the warm and humid climate inferred for this region during the upper Pleistocene. The discovery of Qualeoxylon in Arroyo Feliciano Formation supports the hypothesis that the Vochysiaceae was more widespread in the past than today.